Anti-Inflammatory and Antioxidant Properties of Carvacrol and Magnolol, in Periodontal Disease and Diabetes Mellitus - Cicalău, Georgiana; Babes, Petru; Calniceanu, Horia; Popa, Adelina; Ciavoi, Gabriela; Iova, Gilda; Ganea, Mariana; Scrobotă, Ioana (Molecules (Basel, Switzerland), 2021)
Periodontal disease and diabetes mellitus are two pathologies that are extremely widespread worldwide and share the feature of chronic inflammation. Carvacrol is a phenolic monoterpenoid, produced by a variety of herbs, the most well-known of which is Origanum vulgare. Magnolol is a traditional polyphenolic compound isolated from the stem bark of Magnolia officinalis, mainly used in Chinese medicine. The purpose of this paper is to review the therapeutic properties of these bioactive compounds, in the treatment of periodontitis and diabetes. Based on our search strategy we conducted a literature search in the PubMed and Google Scholar databases to identify studies. A total of one hundred eighty-four papers were included in the current review. The results show that carvacrol and magnolol have anti-inflammatory, antioxidant, antimicrobial, anti-osteoclastic, and anti-diabetic properties that benefit both pathologies. Knowledge of the multiple activities of carvacrol and magnolol can assist with the development of new treatment strategies, and the design of clinical animal and human trials will maximize the potential benefits of these extracts in subjects suffering from periodontitis or diabetes.